Răspuns :
daca x ≥ 0 ⇒ x√2 = √x²·√2 = rad ( 2x² )
daca a ≥0 -3a√5 = - √9·√a²·√5 = - rad( 45a²)
3x²√2 = √9·√x⁴√2 = rad ( 18x⁴ )
- 4a²√15 = - √16√a⁴√15 = - rad ( 16 ·15a⁴ ) = - rad( 240a⁴ )
x≥ 0 ; x√6x = √x²·√6x = rad(x² ·6x ) = rad( 6x³ )
b >0 ; b√6a²/b = rad( b²·6a² / b ) = rad( 6a²b)
x > 0 ; -6x³√2 /x³ = - rad( 6²·x⁶ ·2 / x³ ) = - rad( 72x³ )
a, b ≥ 0 ; 0,(6) = 6 / 9 = 2 / 3
- 2 /3 · a²b√3b = - rad ( 2² ·a⁴b²· 3b / 3² )
= - ( 4·a⁴b³ / 3)
daca a ≥0 -3a√5 = - √9·√a²·√5 = - rad( 45a²)
3x²√2 = √9·√x⁴√2 = rad ( 18x⁴ )
- 4a²√15 = - √16√a⁴√15 = - rad ( 16 ·15a⁴ ) = - rad( 240a⁴ )
x≥ 0 ; x√6x = √x²·√6x = rad(x² ·6x ) = rad( 6x³ )
b >0 ; b√6a²/b = rad( b²·6a² / b ) = rad( 6a²b)
x > 0 ; -6x³√2 /x³ = - rad( 6²·x⁶ ·2 / x³ ) = - rad( 72x³ )
a, b ≥ 0 ; 0,(6) = 6 / 9 = 2 / 3
- 2 /3 · a²b√3b = - rad ( 2² ·a⁴b²· 3b / 3² )
= - ( 4·a⁴b³ / 3)
x√2=√x²*2=√2x²
-3a√5=√(-3a)²*5=√9a²*5=√45a²
3x²√2=√(3x²)²*2=√9x⁴*2=√18x⁴
-4a²√15=√(4a²)²*15=√16a⁴*15=√240a⁴
x√6x=√x²*6x=√6x³
(b√6a²)/b=√(b²*6a²)/b=√6a²b
(-6x³√2)/x³=√((-6x³)²*2)/x³=√72x³
-0,(6)a²b√3b=-6/9a²b√3b=√(-6/9*a²b)²*3b=√(4a⁴b³)/3
-3a√5=√(-3a)²*5=√9a²*5=√45a²
3x²√2=√(3x²)²*2=√9x⁴*2=√18x⁴
-4a²√15=√(4a²)²*15=√16a⁴*15=√240a⁴
x√6x=√x²*6x=√6x³
(b√6a²)/b=√(b²*6a²)/b=√6a²b
(-6x³√2)/x³=√((-6x³)²*2)/x³=√72x³
-0,(6)a²b√3b=-6/9a²b√3b=√(-6/9*a²b)²*3b=√(4a⁴b³)/3